Research Progress of Air Source Heat Pump Heat Storage System - Ni Long; Zhou Chaohui; Yao Yang; Jiang Yiqiang (Zhileng xuebao)
The combination of heat storage technology and air source heat pump (ASHP) can provide heat source for air source heat pump defrosting, solve the problem of variable heat due to the fluctuation of outdoor air parameters, alleviate the contradiction between supply and demand, and perform an important function on the peak load shifting. Through the review of the application of heat storage technology in ASHP, this paper introduces the air source heat pump heat storage defrosting system, the effect of air source heat pump in heating regulation and electric peak-shaving, and its application as a heat pump water heater in hot water supply. It is pointed out that air source heat pump heat storage system will play an important role in defrosting, heating, water heater and electric peak-shaving in the future. The selection and dosage of heat storage materials, the lectotype and volume of heat storage tanks will be the future research directions.